Crossed Renal Ectopia without Fusion: An Uncommon Cause of Abdominal Mass - Ana Ratola; Maria Miguel Almiro; Rita Lacerda Vidal; Nuno Neves; Adelaide Bicho; Sofia Figueiredo (Case Reports in Nephrology)
Crossed renal ectopia is a rare congenital anomaly usually associated with fused kidneys (90%). Most cases are asymptomatic and remain undiagnosed. We report an unusual case of nonfused crossed renal ectopia. The 11-year-old adolescent female patient was admitted with abdominal pain, anorexia, weight loss, and periumbilical mass. Although the initial clinical suspicion was a tumoral lesion, abdominal ultrasound and magnetic resonance examination revealed crossed renal ectopia without fusion. The renal ectopy was incidentally diagnosed, as described in 20 to 30% of cases. In this case, the associated nonspecific symptoms were a coincidence.